Converging theories on dreaming: Between Freud, predictive processing, and psychedelic research - Koslowski, Michael; de Haas, Max-Pelgrom; Fischmann, Tamara (Frontiers in Human Neuroscience, 2023)
Background: In this article the authors try to connect the fields of dream research, the predictive processing account of human cognition, affective neuroscience, neuropsychoanalysis, and the emerging research on psychedelic substances, in order to deepen our understanding of the mechanisms of the dreaming brain and dream-like states. Methods: The core concepts of the mentioned theories are presented, compared, combined and further developed in regard to a better understanding of the formation, function and dynamic of dreams and dream-like states. Results: The repressed priors (M. Solms) from the predictive processing perspective might correspond to the conflictual complexes (U. Moser) from empirical dream research. The similarities of pharmacologically induced altered states of consciousness via dreams and 5HT-2A-R-agonists (psychedelics) are analyzed, particularly regarding typical changes in cognition, affectivity, and sense of self. Conceptual bridges between theories of consciousness, dream research and neurobiological accounts are proposed, to further advance in empirical studies on the nature and different functions of dreaming. Conclusions: Insights from research with dream-like states could be used to inform dream research and related therapeutic techniques, and vice versa. Further empirical research questions and methods are proposed.